2021
DOI: 10.2991/assehr.k.211220.307
|View full text |Cite
|
Sign up to set email alerts
|

The External and Internal Factors of Academic Burnout

Abstract: Academic burn-out is a common phenomenon among students. Because of the long-term academic pressure and burden, students feel exhausted, lose enthusiasm for their studies and activities, and hold a negative attitude towards learning. This study aimed to research academic burn-out and summarize the influencing factors of academic burn-out. The present study divides the influencing factors into external factors and internal factors. External factors include school factors (learning pressure, teaching environment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 41 publications
0
5
0
2
Order By: Relevance
“…The present study was conducted on a group of university students from Hidalgo, Mexico. This region of Mexico presents a higher level of poverty and inequality and since it is suggested that the SES plays a determining role in the development of academic SB, our findings could be generalizable only to populations with similar socioeconomic characteristics (Merritt & Buboltz, 2015;Lin & Yang, 2021).…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…The present study was conducted on a group of university students from Hidalgo, Mexico. This region of Mexico presents a higher level of poverty and inequality and since it is suggested that the SES plays a determining role in the development of academic SB, our findings could be generalizable only to populations with similar socioeconomic characteristics (Merritt & Buboltz, 2015;Lin & Yang, 2021).…”
Section: Discussionmentioning
confidence: 81%
“…Regarding socioeconomic characteristics, unlike Mexico, Spain, and Italy have a higher human development index, which is related to the economic condition of a country (United Nations Development Programme, 2020). Data suggest higher levels of BS in students from families with low socioeconomic status (SES; Lin & Yang, 2021). The SES represents the availability of resources to cover expenses related to compliance with academic requirements (i.e., payment for transportation, purchase of books, uniforms, or materials; Merritt & Buboltz, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the school level, elevated school demands (i.e., authority conflict, emotional and mental demands), learning pressure, poor interpersonal relationships, and a negative teaching environment were positively related to burnout symptoms, while school resources (i.e., teacher support, control, autonomy) showed a negative association to burnout symptoms [ 20 , 21 ]. Concerning family factors, parenting style, family economic status, and parental support and acceptance have been found to influence burnout symptoms [ 20 , 22 , 23 ]. Further, elevated levels of life stress positively predict academic burnout in student samples [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…[8]A resource based model environment to understand your specific situation, recognize your competitive mind, and get to follow more developmental growth.. (Fangyu L. , Kaidan Y. 2021) [4]According to social identity theory, the proposed framework suggests that when employees identify strongly with the organization, this affects the way employees view external stakeholders in the social landscape at work, thus promoting some more and better consequences. (DANIEL KORSCHUN, 2015) It is beneficial for corporate enterprise development.…”
Section: Introductionmentioning
confidence: 99%